Implementasi Kesatuan Gereja Berdasarkan Reinterpretasi Frase Pasa Oikodomi Dalam Efesus 2:21 - Kiamani, Andris; Pattinaja, Aska Aprilano; Harefa, Darmianus (Sekolah Tinggi Teologi Baptis Indonesia, 2025)
This research article aims to reinterpret the true meaning of the phrase πᾶσα οἰκοδομὴ (Pasa Oikodomi) in Ephesians 2:21. There are two interpretations in translating the phrase, namely in the literal sense as the temple and in the metaphorical sense as a symbolization of the church as the Body of Christ. If so, what is the true meaning of the phrase πᾶσα οἰκοδομὴ (Pasa Oikodomi)? To answer this question, this research is conducted through a specific and comprehensive study of the reinterpretation of the phrase πᾶσα οἰκοδομὴ (pasa oikodomi). Based on the use of interpretative qualitative method through hermeneutic process, this article finds that the reinterpretation of the phrase πᾶσα οἰκοδομὴ (Pasa Oikodomi) refers to the whole body, and or the whole congregation in the unity of the church. The basic argument of the reinterpretation is that, in the context of the letter to the Ephesians, Paul is talking about unity in the body of Christ, namely the church. Therefore, the novelty of this research lies in its comprehensive hermeneutical approach, which affirms the phrase πᾶσα οἰκοδομὴ (Pasa Oikodomi) as an affirmation of the unified structure of the church as the body of Christ, rather than merely a symbol of a physical building.